PENGARUH STAKEHOLDER PRESURE DAN CORPORATE GOVERNANCE TERHADAP KUALITAS SUSTAINABILITY REPORT PERUSAHAAN - Mulyaji Dharmawan (2023)
This research is a quantitative study that aims to determine the effect of stakeholder pressure using employee, shareholder and corporate governance mechanisms using the board of commissioners and audit committee mechanisms on the quality of sustainability reports. This research uses a sample of 35 non financial sector companies listed on the IDX in the 2018-2021 period. In this research, secondary data is used whose sources come from annual reports and sustainability reports which can be accessed via the Indonesian Stock Exchange website and websites of related entities. This study uses a random effect model with panel data regression, the process of processing the data is done using STATA version 16